Study on the Knowledge, Attitude, and Practice (KAP) of Nursing Staff and Influencing Factors on COVID-19 - Wen, Xin; Wang, Fan; Li, Xiuyang; Gu, Hua (Frontiers in Public Health, 2021)
To investigate the knowledge, attitude and practice (KAP) on Coronavirus Disease 2019 (COVID-19) care among nursing staff and analyze its influencing factors. The survey was conducted on February 18, 2020 among 7,716 voluntary participants from 143 medical institutions in Zhejiang, China. The finding indicated that knowledge, attitude and practice of nursing staff scored well. But the accuracy of psychological nursing knowledge was much lower, 14.3 percent only. Nursing staff working in isolation wards have higher knowledge, attitude and practice scores than those in general wards, the OR values were 1.776(1.491 2.116), 1.542(1.298 1.832), 1.902(1.590 2.274), respectively. Nursing staff with working experience of less than 10 years had lower knowledge, attitude and practice scores than those with more than 20 years, the OR values were 0.490(0.412 0.583), 0.654(0.551 0.775), 0.747(0.629 0.886). It is necessary to take measures to enhance the training on COVID-19, especially for knowledge, attitude and practice of junior nurses in general wards.